2001
DOI: 10.1023/a:1016688110279
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing images in dreams: More intense after abuse and trauma.

Abstract: A contextualizing image (Cl) is a poweiful central image in a dream which can be seen as picturing, or providing a picture-context for, the dominant emotion of the dreamer. Thus the paradigmatic dream, HI was overwhelmed by a tidal wave," contextualizes the dominant emotion of fear/terror or helplessness. This study examined the question of whether CIs, scored on a blind basis, are especially frequent and intense in persons who have suffered abuse, and in persons who have suffered a recent acute trauma.Two set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 10 publications
6
51
1
Order By: Relevance
“…There is some clinical evidence that the content and structure of dreaming change over time after a traumatic experience, indicating the dreamer's attempts at psychological adjustment (Hartmann, Zborowski, Rosen, & Grace, 2001). At first, dreams portray the traumatic event exactly as it has happened, typically involving images of extreme threat, helplessness and terror.…”
Section: Dreaming and Mental Healthmentioning
confidence: 99%
“…There is some clinical evidence that the content and structure of dreaming change over time after a traumatic experience, indicating the dreamer's attempts at psychological adjustment (Hartmann, Zborowski, Rosen, & Grace, 2001). At first, dreams portray the traumatic event exactly as it has happened, typically involving images of extreme threat, helplessness and terror.…”
Section: Dreaming and Mental Healthmentioning
confidence: 99%
“…CI is a construct to represent the intensity of the image and can be scored. Trauma survivors had statistically significant differences in the CI score compared to a control group, and emotion rates as contextualized tended toward more negative emotions; especially pronounced were the affects involving fear/terror and helplessness vulnerability (Hartmann et al, 2001). Phelps et al (2011) found similar results among PTSD survivors.…”
Section: Dreams Images and The Unconsciousmentioning
confidence: 82%
“…Hartmann et al, (2001) introduce the notion of contextualizing images (CI) in dreamsa powerful central image that provides context for the dominant affect within the dream. CI is a construct to represent the intensity of the image and can be scored.…”
Section: Dreams Images and The Unconsciousmentioning
confidence: 99%
See 1 more Smart Citation
“…Ernest Hartmann’s research group [95 ]has developed a reliable system for scoring the intensity and emotional quality of such images. Hartmann et al [96] found that dream reports from students reporting a history of abuse produced significantly more intense contextualizing images than did reports of non-abused students. Comparing dream reports from 16 subjects regularly recording their dreams, Hartmann and Basile [94] detected a strong increase in intensity of the dream imagery after the 9/11 attacks.…”
Section: The Content Of Posttraumatic Nightmaresmentioning
confidence: 99%